The Portrayal of Seneca in the Octavia and in Tacitus’ Annals - Pigoń, Jakub (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The paper examines the representation of Seneca in two literary works of the late 1st and early 2nd centuries AD, the anonymous tragedy Octavia and the Annals by Tacitus. In the Octavia Seneca appears as the emperor Nero’s upright but unhappy teacher trying in vain to inculcate salutary advice to his master. There is no question of his being responsible for the crimes of Nero; the picture of him drawn in the play is wholly favourable. The portrayal of Seneca in Tacitus’ Annals is more complex and nuanced, and only seldom does the historian give his own views about Nero’s advisor. However, it would be wrong to suppose that Seneca is harshly criticised by Tacitus.